Gambaran Efikasi Diri Pasien Diabetes Mellitus - Yusvita Walia; Hema Malini; Elvi Oktarina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aimed to see a picture of self-efficacy in patients with diabetes mellitus at the Padang Pariaman Health Center. The method used is a quantitative research method with a descriptive design with a survey approach. The sample in this study was 92 respondents. The results showed that of the 92 respondents with good self-efficacy, as much as 42.4%, while 57.6% had poor self-efficacy. In conclusion, self-efficacy in diabetes mellitus patients will affect patients in behaving and being committed so that the goals of the desired behavior change can be achieved with self-efficacy. Individuals with solid self-efficacy have high hopes for the success of achieving goals, while individuals with low self-efficacy have doubts about achieving their goals. Keywords: Diabetes Mellitus, Self Efficacy, Chronic Disease